2008
DOI: 10.1088/1751-8113/41/33/335205
|View full text |Cite
|
Sign up to set email alerts
|

Viscous potential flow analysis of capillary instability with heat and mass transfer

Abstract: We carry out the linear viscous-irrotational analysis of capillary instability with heat transfer and phase change. We consider the cylindrical interface shared by two viscous incompressible fluids enclosed by two concentric cylinders. In viscous potential flow, viscosity enters the model through the balance of normal stresses at the interface. We write the dispersion relation from the stability analysis for axisymmetric disturbances in terms of a set of dimensionless numbers that arise in this phase change pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 11 publications
2
29
0
Order By: Relevance
“…They observed that the heat and mass transfer has a stabilizing effect when the lower fluid viscosity is high and destabilizing effect when lower fluid viscosity is low. Kim et al [9] investigated the capillary instability problem of vapor liquid system in an annular configuration with heat and mass transfer using viscous potential flow for axisymmetric disturbances. They observed that for irrotational motion of two viscous fluids, heat and mass transfer phenomenon completely stabilizes the interface against capillary effects.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the heat and mass transfer has a stabilizing effect when the lower fluid viscosity is high and destabilizing effect when lower fluid viscosity is low. Kim et al [9] investigated the capillary instability problem of vapor liquid system in an annular configuration with heat and mass transfer using viscous potential flow for axisymmetric disturbances. They observed that for irrotational motion of two viscous fluids, heat and mass transfer phenomenon completely stabilizes the interface against capillary effects.…”
Section: Introductionmentioning
confidence: 99%
“…In Eq. (32) putting H 0 = 0, ε = 1, k 1 → ∞ we get the dispersion relation as obtained by Kim et al [7]. Choosing…”
Section: Dispersion Relationmentioning
confidence: 76%
“…The effect of heat and mass transfer on the Kelvin-Helmholtz instability was studied by Asthana and Agrawal [6] when both fluids are miscible and viscous. Kim et al [7] extended the work of Funada and Joseph [1] including the effect of interfacial heat and mass transfer. They have found that the interfacial heat and mass transfer phenomenon resists the growth of disturbance waves.…”
mentioning
confidence: 99%
“…Therefore, Ca has a stabilizing effect on the stability of the system. Kim et al [17] have also observed that the heat and mass transfer phenomenon has stabilizing effect in the absence of magnetic field and therefore, magnetic field does not affect the behavior of magnetic field. The effect of heat and mass transfer on the stability of the system can be explained in terms of local evaporation and condensation at the interface.…”
Section: Resultsmentioning
confidence: 98%
“…They observed that the heat and mass transfer has a stabilizing effect when the lower fluid viscosity is high and destabilizing effect when fluid viscosity is low. Kim et al [17] investigated the capillary instability problem of vapor liquid system in an annular configuration with heat and mass transfer using viscous potential flow for axisymmetric disturbances. Awasthi and Agrawal [18] have studied the nonlinear effects on the capillary instability in the presence of heat and mass transfer and observed that heat and mass transfer phenomenon has stabilizing effect on the stability of the system in the nonlinear analysis.…”
Section: Introductionmentioning
confidence: 99%